FAKTOR-FAKTOR YANG MEMPENGARUHI MIGRASI MASUK RISEN DI PROVINSI KALIMANTAN TIMUR - Rachmad Budi Suharto (Jurnal Ekonomi dan Manajemen, 2018)
This research aimed to tasted the influence of wages, the influence of employment, investment and capital expenditures on migration in risen in east kalimantan.The theory that used demographic.This research using secondary data in the form of panel, analyzed using panel data regression analysis.The testing of hypotheses use the assumption classic, R test, R2, who has been adjusted F test and T test and analyzed quantitatively using computer program SPSS ( statistical package for the social science ) 20.The result of this research shows that wages have negative effects but insignificant, employment influential positive and significant, investment it has some positive effects but insignificant, capital expenditures influential positive and significant on migration in risen in east kalimantan.